Worldwide destinations casebook : the geography of travel and tou rism - Boniface, Brian G.; Cooper, Chris, 1952- (Oxford : Butterworth-Heinemann, 2005)
"Worldwide destinations casebook provides 36 comprehensive case stud ies of international tourism destinations. A companion text to the core textbook Worldwide destinations, 4th ed., these cases contextualize th e learning and provide real life illustrationsof the theories covered" -- Cover, p. 4.
Includes bibliographical references and index.
Keywords: Tourism; Travel